KESEPIAN DENGAN KESEJAHTERAAN SUBJEKTIF PADA USIA LANJUT YANG TINGGAL DI PANTI JOMPO KHUSNUL KHOTIMAH PEKANBARU RIAU - Mulya Sasmita; Alma Yulianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
This research study the correlation between loneliness and subjective well being in elderly people at nursing home. Samples are 27 male and 23 female taken by purposive random sampling. Reliablity of loneliness is (α) 0.912 and (α) 0.891 for subjective well being. Data analysis used product moment correlation. Result shows negative correlation between loneliness and subjective well being with confident correlation is (r) -0.700 (p= 0.000)